Implementation and simulation of a synchronverter (2017)
When integrating renewable energies to the grid, usually is necessary the use of a converter to adapt the voltage and frequency. As generation is changing to a distributed scheme an issue that arises, is that these converters do not provide enough inertia. A possible solution is using a converter that mimics the behaviour of a synchronous generator, i.e. a synchronverter. In this project the implementation and simulation, both online and offline, of a synchronverter are performed. A bibliographical review is made to contextualize the reader, then a synchronous generator and a typical inverter are implemented. These modules are used to build the synchronverter which is connected to the grid and other synchronverter. Analysis based on the frequency, voltage, current and power are performed, for both transient and steady state. Finally, sensibility tests are carried out. Synchronverter demonstrates good overall performance and shows as a feasible way to improve the integration of converter-dependant renewable sources